2015
DOI: 10.3390/jmse3020412
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction for Growth in Atlantic Cod (Gadus morhua L.) in Four Farms of Norway

Abstract: We studied genotype by environment interaction (G × E) for body weight (BW) of Atlantic cod (Gadus morhua L.) from the National cod breeding program in Norway. Records of 13,811 fish in a nucleus farm (NUC) and two test farms (PENorth, PESouth) in year-class (YC) 2007, and for 9149 fish in NUC and one test farm in YC 2010 were available. Heterogeneity of variances and heritabilities () were estimated using a univariate animal model with environmental effects common to full-sibs (full-model). Genetic correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Model Description), lending good empirical support to this model and providing evidence for more strongly density-dependent growth. However, aquaculture studies of Atlantic cod (62,63) suggest a high genetic variance in growth, and previous studies of other species found evidence for harvest-induced evolution of growth (10,29,64,65), suggesting that weaker density dependence and more evolution of growth are possible. Another possibility is that the strength of density-dependent growth has varied over time, which could happen if, for example, ecosystem conditions have changed (66,67).…”
Section: Discussionmentioning
confidence: 89%
“…Model Description), lending good empirical support to this model and providing evidence for more strongly density-dependent growth. However, aquaculture studies of Atlantic cod (62,63) suggest a high genetic variance in growth, and previous studies of other species found evidence for harvest-induced evolution of growth (10,29,64,65), suggesting that weaker density dependence and more evolution of growth are possible. Another possibility is that the strength of density-dependent growth has varied over time, which could happen if, for example, ecosystem conditions have changed (66,67).…”
Section: Discussionmentioning
confidence: 89%
“…Another thing to consider in a giant gourami selection program is an environmental cultivation factor. As reported by [3] that aquaculture, ecological variables can affect fish growth performance throughout the production environment. The difference between ecological variables can induce a *Corresponding author: mmlitbang@gmail.com phenomenon called genotype interaction by the environment.…”
Section: Introductionmentioning
confidence: 92%
“…There is a possible change in ranking genotype performance in different environments, which is the best genotype in one production environment may not be the best in another production environment. As confirmed by [3], selection based on one environment can reduce genetic advantages in other production environments.…”
Section: Introductionmentioning
confidence: 93%
“…Consequently, several studies have focused on estimation of the heritability of body weight traits across the production cycle: at tagging, 1+ of age, at 2 years, 2.5 years/harvest. Overall, moderate to high estimates of heritability have been reported for body weight at different stages of production, 56,162,164‐167 with exception of Bangera et al 168 who estimated mainly low heritability for 2.5‐year body weight at different geographical locations. Body weight measurements registered close together are genetically highly correlated, whereas more distant body weight measurements are less genetically correlated 56,166 …”
Section: Establishment Of Norwegian Selective Breeding Programme For Codmentioning
confidence: 97%